Trend Moment Method to Predict Sales of Pekanbaru Hoya Bread - Siregar, Wahyuni; Syah, Arridha Zikra; Harahap, Indra Ramadona (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Hoya or better known as Hoya Bakery is located on Durian Street, Pekanbaru City. Is one of the shops and factories that produce and sell various kinds of bread and market snacks located in various places in Pekanbaru. Especially in meeting the demand that will be distributed to consumers which is relatively large so that there are often out of stock bread and excess stock. Therefore, accurate and efficient predictions of bread sales are needed using the trend moment method. A forecast to produce forecasts of bread supplies in the future. In this study, data on bread sales are used every month from October 2019 to September 2020. The sales record for each month is useful to see whether it has increased or decreased. The result of this research is the creation of a computerized system that is able to generate estimates for the next month using the PHP and MySQL programming languages, making it easier to find out how much bread will be sold and consider how much will be produced in the following month so that there is no shortage or excess stock of bread